Peningkatan Kompetensi Khatib Berbasis Digital Melalui Pelatihan E-Modul Khatib Profesional - Sobri, Muhammad; Vahlepi, Sahrizal; Supian, Supian; Soleh, Warisuddin; Jamil, Helmun (Penerbit Widina, Widina Media Utama, 2025)
This community service program aims to strengthen khutbah competencies through professional khatib e-module training for students of the Arabic Language Education Study Program, Faculty of Teacher Training and Education, Universitas Jambi. The program was motivated by students’ limited khutbah skills, such as low self-confidence, poorly structured sermon texts, and inadequate mastery of rhetoric and fiqh of khutbah. The training employed the Participatory Action Research (PAR) approach, emphasizing active participation of students in planning, implementation, and evaluation. The results showed significant improvements in knowledge, skills, and attitudes. Students became more capable of composing structured khutbah texts, delivering them with persuasive rhetoric, and performing with greater self-confidence. This program also contributed to the achievement of the Merdeka Belajar Kampus Merdeka (MBKM) policy and the university’s Key Performance Indicators (IKU). Thus, the professional khatib e-module is proven effective as an innovative training medium to develop professional young khatibs who are academically competent and socially impactful.ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat kompetensi khatib melalui pelatihan e-modul khatib profesional pada mahasiswa Prodi Pendidikan Bahasa Arab FKIP Universitas Jambi. Latar belakang program ini berangkat dari fenomena lemahnya keterampilan khutbah mahasiswa, seperti kurang percaya diri, penyusunan teks khutbah yang belum terstruktur, serta minimnya penguasaan retorika dan fikih khutbah. Pelatihan dilaksanakan dengan pendekatan Participatory Action Research (PAR) yang menekankan partisipasi aktif mahasiswa dalam perencanaan, pelaksanaan, hingga evaluasi. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada aspek pengetahuan, keterampilan, dan sikap mahasiswa. Mahasiswa mampu menyusun teks khutbah yang lebih sistematis, menyampaikannya dengan retorika persuasif, serta menampilkan rasa percaya diri yang lebih tinggi. Program ini juga mendukung capaian Merdeka Belajar Kampus Merdeka (MBKM) dan Indikator Kinerja Utama (IKU). Dengan demikian, e-modul khatib profesional efektif sebagai media pelatihan inovatif untuk mencetak khatib muda yang profesional dan berdaya guna.